Srebrenica in the aftermath of genocide - Nettelfield, Lara J.; Wagner, Sarah E., 1972- (New York : Cambridge University Press, 2014)
The fall of the United Nations'safe area'of Srebrenica in July 1995 to Bosnian Serb and Serbian forces stands out as the international community's most egregious failure to intervene during the Bosnian war. It led to genocide, forced displacement and a legacy of loss. But wartime inaction has since spurred numerous postwar attempts to address the atrocities'effects on Bosnian society and its diaspora. Srebrenica in the Aftermath of Genocide reveals how interactions between local, national and international interventions - from refugee return and resettlement to commemorations, war crimes trials, immigration proceedings and election reform - have led to subtle, positive effects of social repair, despite persistent attempts at denial. Using an interdisciplinary approach, diverse research methods, and more than a decade of fieldwork in five countries, Lara J. Nettelfield and Sarah E. Wagner trace the genocide's reverberations in Bosnia and abroad. The findings of this study have implications for research on post-conflict societies around the world.
Introduction: Intervention and its meanings -- Memorializing Srebrenica -- The politics and practice of homecoming: refugee return -- Special status for a special crime -- Srebrenica abroad : diaspora activism and controversies -- Immigration violations in the US : a different kind of accounting -- Srebrenica in court -- Pushing back : denial -- Conclusion
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: masakr ve Srebrenici (1995 : Srebrenica, Bosna a Hercegovina); válka v Bosně a Hercegovině (1992-1995); válečné zločiny -- Bosna a Hercegovina; genocida -- Bosna a Hercegovina; poválečná obnova -- Bosna a Hercegovina; demokratizace -- Bosna a Hercegovina; Srebrenica massacre (1995 : Srebrenica, Bosnia and Herzegovina); Bosnia and Herzegovina, civil war (1992-1995); war crimes -- Bosnia and Herzegovina; genocide -- Bosnia and Herzegovina; postwar reconstruction -- Bosnia and Herzegovina; democratization -- Bosnia and Herzegovina; Srebrenica (Bosna a Hercegovina); Srebrenica (Bosna a Herzegovina); monografie; e-knihy online; monographs; e-books online